Where is crystallography going?. Issue 2 (4th February 2018) - Grimes, Jonathan M.; Hall, David R.; Ashton, Alun W.; Evans, Gwyndaf; Owen, Robin L.; Wagner, Armin; McAuley, Katherine E.; von Delft, Frank; Orville, Allen M.; Sorensen, Thomas; Walsh, Martin A.; Ginn, Helen M.; et al.
Abstract : Macromolecular crystallography has provided results that underpin much biological discovery and there is still scope for further development; however, a revolution in electron imaging now means that it can also routinely provide detailed atomic‐level descriptions. This article attempts to tease out where crystallography is going and consider what its place might be in the new landscape. Abstract : Macromolecular crystallography (MX) has been a motor for biology for over half a century and this continues apace. A series of revolutions, including the production of recombinant proteins and cryo‐crystallography, have meant that MX has repeatedly reinvented itself to dramatically increase its reach. Over the last 30 years synchrotron radiation has nucleated a succession of advances, ranging from detectors to optics and automation. These advances, in turn, open up opportunities. For instance, a further order of magnitude could perhaps be gained in signal to noise for general synchrotron experiments. In addition, X‐ray free‐electron lasers offer to capture fragments of reciprocal space without radiation damage, and open up the subpicosecond regime of protein dynamics and activity. But electrons have recently stolen the limelight: so is X‐ray crystallography in rude health, or will imaging methods, especially single‐particle electron microscopy, render it obsolete for the most interesting biology, whilst electron diffraction enables structure determination from even the smallest crystals? We will lay out some information to help you decide.